2017
DOI: 10.1002/stem.2607
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Inducible Gene 1 Protein (RIG1)-Like Receptor Pathway Is Required for Efficient Nuclear Reprogramming

Abstract: We have revealed a critical role for innate immune signaling in nuclear reprogramming to pluripotency, and in the nuclear reprogramming required for somatic cell transdifferentiation. Activation of innate immune signaling causes global changes in the expression and activity of epigenetic modifiers to promote epigenetic plasticity. In our previous papers, we focused on the role of toll-like receptor 3 (TLR3) in this signaling pathway. Here we define the role of another innate immunity pathway known to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…IPS-1 is an intermediary protein that is required for RLR-dependent IFN production in response to virus infection [93]. Knockdown of iPS-1, the common adaptor protein for the RLR family, substantially reduced nuclear reprogramming [2]. In addition, we found that LPS, an agonist of TLR4, also promotes the reprogramming mechanism (unpublished data).…”
Section: Innate Immune Signaling and Nuclear Reprogramming To Pluripomentioning
confidence: 72%
See 3 more Smart Citations
“…IPS-1 is an intermediary protein that is required for RLR-dependent IFN production in response to virus infection [93]. Knockdown of iPS-1, the common adaptor protein for the RLR family, substantially reduced nuclear reprogramming [2]. In addition, we found that LPS, an agonist of TLR4, also promotes the reprogramming mechanism (unpublished data).…”
Section: Innate Immune Signaling and Nuclear Reprogramming To Pluripomentioning
confidence: 72%
“…These fibroblast-derived induced endothelial cells (iECs) expressed all of the expected immunohistochemical markers; manifested endothelial functions not present in fibroblasts (eg. generation of nitric oxide, formation of tubular networks in matrigel; uptake of acetylated LDL); and had a transcriptional profile (by RNA seq studies) that was highly similar to genuine endothelial cells [2]. Expected histone modifications were observed in the iECs (such as increased H3K4me3 and decreased H3K27me3 in endothelial specific gene promoters such as CD31).…”
Section: Innate Immune Signaling and Transdifferentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, we hypothesized that these cytoplasmic proteins, which regulate inflammatory and apoptotic responses could also enhance nuclear reprogramming. Our hypothesis was further strengthened when our attempt to reprogram fibroblasts from TLR3-knockout mice failed to completely abolish nuclear reprogramming, thereby suggesting that other pathways might also be involved (Sayed et al, 2017 ). Knockdown of the RLR pathway partially inhibited reprogramming, while addition of the RLR ligand enhanced the process, suggesting that RLR pathways are yet another PRR that might be involved in viral-based nuclear reprogramming (Sayed et al, 2017 ).…”
Section: “Toll” On the Road To Nuclear Reprogrammingmentioning
confidence: 91%